PELATIHAN DIGITAL MARKETING DI PAROKI JATIWARINGIN ST. LEO AGUNG - Wawa Santoso; Nila Pusvikasari; Ian Nurpatria Suryawan; Klemens Wedanaji Prasastyo (Jurnal Abdimas Bina Bangsa, 2023)
Community service activities as a form of service to the community who need supporting activities so that they can be carried out properly. For this reason, P3M Trisakti School of Management is collaborating with relevant agencies, in this case the SME Paroki Jatiwaringin St. Leo Agung division. P3M Trisakti School of Management conducted training on digital marketing for SME activists at Paroki Jatiwaringin St. Leo Agung division the Great in Jakarta. SME activists must have ideas in making products / services. The idea must be based on the desires and requests of consumers, and consumers must be able to buy it and make it possible to make this idea a reality. This digital marketing training method uses case study explanations that have been carried out by SME activists who have had successful businesses and reference material regarding digital marketing including material on how to create an account on the Lazada, Shopee, Blibli.com marketplaces and other marketplaces. After the training, it is hoped that SME activists at Paroki Jatiwaringin St. Leo Agung division can increase sales of their products/services through the use of sales using the existing marketplace application